Efeito do extrato de produção e estação do ano sobre a qualidade do leite de vacas leiteiras mestiças - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
Among the factors that are related to milk quality, seasonal variations and productive practices stand out. The objective of this study was to evaluate the effect of the production extract and season of the year on the milk quality of crossbred cows. The experiments were conducted in the West-Goiano region, and the samples were collected individually, per animal, from nine properties according to three production extracts: Extract 1 (up to 150 L / day), Extract 2 (> 150 ≤ 500 L / day) and Extract 3 (> 500 L / day), in four instants according to the season: Season 1: summer, Season 2: autumn, Season 3: winter, and Season 4: spring. The milk samples were analyzed at the milk quality laboratory of the Veterinary and Animal Science School of the Federal University of Goiás, regarding fat, protein, casein, milk nitrogen, lactose, total solids, non-fat solids, bacterial count total and somatic cell counts. The results of total bacterial count and somatic cell counts were logarithmic. The experimental design was completely randomized, the data collected was submitted to analysis of variance and the means were compared to the Tukey test at 5% through the program SISVAR version 5.6. There was no significant effect of the production extract on fat, protein, casein, lactose and somatic cell counts. However, there was an effect of the production extract on the levels of urea nitrogen in the milk, with the highest concentrations evident in the properties of Extract 3 (15.18 mg / dL) and in the total bacterial count, where the highest average was in Extract 1 (5.73 log CFU / mL). The seasonal effect of the total bacterial count was observed, with the lowest mean in winter (4.96 log CFU / mL). Thus, it was detected that the production extract and the season of the year, were related to variations in ureic nitrogen in the milk and total bacterial count.
Keywords: Bovino; Composição do leite; Período do ano; Produtividade; Bovine; Milk composition; Period of the year; Productivity.; CIENCIAS AGRARIAS